Seasonal drivers of picoeukaryotic community structure and assembly in complex aquatic systems: A case study of the Changjiang (Yangtze) River Estuary and East China Sea - Ran Li; Wenxin Fan; Xianghui Guo; Yan Bai; Ping Sun; Nianzhi Jiao; Dapeng Xu (Marine Pollution Bulletin, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Boosting lattice oxygen activation and active sites generation via an Mn-O electron bridge for efficient simultaneous oxidation of toluene and NO over Mn5Co4Ce3Ox catalyst - Lei Gao; Yukai Quan; Ping Fang; Dong Xie; Caiting Li; Cheng Sun; Jiahao Zhang; Ruotao Bai; Jingshuo Zhang (Fuel, 2026)

Crustal anisotropic velocity structure beneath California constrained by P and PmP traveltimes: Implications for fluid-promoted creeping along the central San Andreas Fault - Jing Chen; Tianjue Li; Xiao Xiao; Shucheng Wu; Yiming Bai; Guoxu Chen; Bingfeng Zhang; Mijian Xu; Ping Tong (Earth and Planetary Science Letters, 2026)

A fully biomass-derived intrinsically flame-retardant phenolic resin: Robust adhesion, fire-safe coatings, and closed-loop upcycling for multifunctional cellulose fibers - Wei Tan; Lei Tan; Yin Tian; Ying Chang; Guixiang Song; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Chemical Engineering Journal, 2026)

Regenerated cellulose fibers functionalized with lignin-derived boron-containing phenolic networks for durable flame retardancy and UV protection - Wei Tan; Jieyun Zhao; Lei Tan; Yin Tian; Guixiang Song; Ying Chang; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

Isodonoids A–L: Ent-kauranoid diterpenoid-flavanone conjugates from Isodon rubescens - Can-Can Wang; Meng-Yu Bao; Hui-Ying Li; Hao-Ming Xiong; Kei-Fong Ng; Li-Ping Bai; Wei Zhang; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Irrigation enhanced nitrification and hydrological partitioning drive groundwater nitrate accumulation in an agricultural irrigation district - Xu Yang; Ruihong Yu; Guanglei Yu; Yansong Bai; Shen Qu; Dong Qian; Muhan Li; Zeyuan Liu; Ping Miao; Hongli Ma (Journal of Hydrology, 2026)

Identification of stripe rust resistance loci in Gansu wheat landraces using genome-wide association analysis - Zhe Zhang; Yu Zhang; Ying Guo; Xinyi Ye; Rongguang Wu; Xining Zhang; Haozhen Yang; Ping Jin; Shunda Li; Ravi P. Singh; Bin Bai; Fangping Yang; et al. (Theoretical and Applied Genetics, 2026)

Reliability-adaptive graph-cut phase unwrapping for InSAR geohazard deformation monitoring - Huadong Hu; Ping Zhang; Zhen Li; Jiangyuan Zeng; Haiwei Qiao; Yanan Bai; Siqing Xu; Hui Yuan (International Journal of Remote Sensing, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

Potential targets of baicalein in macrophages revealed by bulk and single cell RNA sequencing analysis - Ping Li; Jianran Hu; Yan Zhang; Xia Bai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rhizosphere metabolic responses to soil acidification and their implications for nutrient uptake in eggplant - Tianqi Wang; Muhammad Awais; Xiaoyang Yu; Baiyi Bai; Zhen Wang; Ruirui Zhang; Lijie Yu; Dan Zhao; Xing Li; Ping Zhang; Roland Bol; Lijuan Yang (Rhizosphere, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Retrieval of snow depth using synthetic aperture radar: past, current, and future - Zhen Li; Haiwei Qiao; Ping Zhang; Yanan Bai; Huadong Hu (Journal of Hydrology, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

Structural heterogeneity and anisotropy beneath Myanmar: Insights into the complex deformation of the Indo-Burma subduction zone - Yiming Bai; Shengji Wei; Jing Chen; Tianjue Li; Bingfeng Zhang; Xiao Xiao; Shucheng Wu; Jiayuan Yao; Yu Wang; Ping Tong (Earth and Planetary Science Letters, 2026)

Synergistic inspiration of in situ growth technology and biomass phytic acid for designing durable flame retardant and antibacterial cellulose fibers - Yin Tian; Wei Tan; Lu Bai; Lei Tan; Ying Chang; Guixiang Song; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Functional Characterization of CsFBK, an F-Box Gene from Camellia Sinensis, Reveals its Negative Regulation of Leaf Angle in tea and Tobacco - Yongqing Bai; Bokun Zhou; Tong Li; Ping Li; Shiyu Tian; Xinzhuan Yao; Litang Lu (Journal of Plant Growth Regulation, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Biodegradable mulch films divergently regulate soil carbon cycle by reshaping microbial communities and functional genes - Haiyun Zhang; Shutong Yu; Weiguang Lv; Xilong Wang; Ping Lu; Hanlin Zhang; Juanqin Zhang; Naling Bai; Chenglong Xu; Xianpu Zhu; Shuangxi Li (Journal of Hazardous Materials, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Oligosaccharide mapping analysis through UPLC-Orbitrap-HRMS and enzymatic hydrolysis from Polygonatum odoratum (Mill.) Druce - Qing-Hua Liu; Liu Yang; Yue Wang; Hao-Ming Xiong; Cai-Yun Wang; Guo-Yuan Zhu; Li-ping Bai; Zhi-Hong Jiang; Wei Zhang (Carbohydrate Polymers, 2026)

Green valorization of invasive alien plants using a novel method of simultaneous hydrothermal treatment and ball milling - Binglei Li; Yi Zhong; Chaoming Li; Xun Tan; Mingquan Lv; Shengjun Wu; Ping Huang; Zhilin Huang; Jiwei Bai; Zhong Chen (Biomass and Bioenergy, 2026)

Genome-Wide Identification and Expression Analysis of the TCP Gene Family in Quinoa (Chenopodium quinoa Willd.) - Yutao Bai; Heng Zhang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Rongbo Li; et al. (Journal of Plant Growth Regulation, 2026)

Suspensaditerpenes A–Q, anti-inflammatory labdane and nor-labdane diterpenoids from the seeds of Forsythia suspensa - Hui-Ying Li; Meng-Yu Bao; Hao-Ming Xiong; Can-Can Wang; Li-Ping Bai; Wei Zhang; Cheng-Yu Chen; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

The appearance of microblade technology at the onset of Marine Isotope Stage 2 in Northeast China - Wei Liu; Jian-Ping Yue; You-Qian Li; Ke-Liang Zhao; Si-Qi Lu; Guang-Yi Bai; Yang Liu; Yu-Xiu Zhang; Shi-Xia Yang (Quaternary Science Reviews, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Maternal linoleic acid intake disrupts early immune-microbiota-fatty acid programming and increases offspring food allergy risk - Tianliang Bai; Chuang Chen; Huming Shao; Fan Yang; Xing Zhang; Ping Tong; Xuanyi Meng; Yong Wu; Hongbing Chen; Xin Li (Food Bioscience, 2026)

Different detoxification strategies of fruit borers adaptation to quercetin - Bing Bai; Huan-Juan Zhao; Bo-Kun Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Identification of homeobox gene family in Chenopodium quinoa and expression patterns in response to flooding stress during the filling stage - Guofei Jiang; Li Li; Yutao Bai; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

CsAHL20 negatively regulates epi-catechins biosynthesis under drought stress in Camellia sinensis - Yu Chen; Mingyuan Luo; Ping Li; Qi Zhao; Luo Chao; Yujie Jiao; Shiyu Tian; Xingyu Tian; Shenyuan Ye; Zhenkedai Yuan; Yilan Hu; Yongqing Bai; et al. (Plant Science, 2025)

Organic matter from spent paper cooking liquor promotes the growth and quality of Chinese chives - Yan Liu; Yuechao Yang; Guiwei Wang; Xiaoqi Wang; Ping Wang; Shan Li; Jiahui Liu; Songyuan Wang; Yijie Bai; Yao Cheng (Journal of Environmental Chemical Engineering, 2025)

Climate-driven microstructural differentiation between loess and paleosol in the Central-Eastern loess Plateau of China - Ping Mo; Aoyang Bai; Yanrong Li (Journal of Asian Earth Sciences, 2025)

Corrigendum to “Geographical origins of Angelica sinensis using functional compounds and multielement with machine learning-based fusion approaches” [Food Chem. 471 (2025) 142747] - Ping Yu; Xinwei Yan; Jiashun Hong; Daocheng Li; Feng Xiong; Ruibin Bai; Jian Yang; Lanping Guo (Food Chemistry, 2025)

Cold crystallization-enabled permanent shape transformation in 4D-printed PLA/TPU composites for personalized wearable devices - Chuanru Zheng; Xi Li; Juan Tan; Anna Tan; Xiuchen Li; Hailiang Ni; Wenhao Yu; Yuefeng Bai; Ping Hu; Wei Min Huang; Hongmei Chen (Chemical Engineering Journal, 2025)

FOXM1 upregulation, promotes immune escape in gastric cancer through activation of Notch signaling pathway - Shangkun Du; Ping Li; Yabin Liu; Bindan Cai; Gang Li; Wenbin Wang; Rui Yan; Xiangkui Zheng; Tianliang Bai (Molecular and Cellular Biochemistry, 2025)

Genome-wide identification and expression analysis of C2H2 zinc finger protein transcription factor in quinoa - Xuqin Wang; Xingmei Zong; Guofei Jiang; Lingyuan Zhang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Identification and comparative genomic analysis of two Bacillus subtilis producing antifungal lipopeptide - Xue Bai; Lina Yi; Shuang Zhao; Jianlong Xiu; Ping Li; Rongjiu Shi; Xiaolong Liang; Ying Zhang (Pesticide Biochemistry and Physiology, 2025)

The deficiencies in texture, organic matter distribution, and active mineral composition of reservoir sediments constrain the formation of healthy soils - Xun Tan; Sidong Zeng; Binglei Li; Shengjun Wu; Ping Huang; Zhong Chen; Xingxing He; Zhilin Huang; Jiwei Bai (Journal of Environmental Management, 2025)

Transcriptome and Metabolome Conjoint Analysis Revealed that PaGLK Affects Photosynthesis and Composition of Root Exudates in Poplar - Xiang-dong Bai; Yu Zheng; Li Cao; Wei Wang; Jing Jiang; Qi-bin Yu; Chuan-ping Yang; Gui-feng Liu (Plant Molecular Biology Reporter, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Ferroptosis: a novel therapeutic warrior in the battle against leukemia - Yiduo Bai; Yizhi Luo; Yiyi Yuan; Xuan Li; Junchang Jin; Ruijing Ping; Jiuru Guo; Liuxu Jin; Yi Yu; Yuyan Xiong (Apoptosis, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Flexural behaviors of GFRP-reinforced Engineered Cementitious Composite (ECC)-concrete composite beams - Li-Hui Wang; Wen-Hao Shi; Lan-Ping Qian; Yu-Lei Bai; Shi-Zhu Liu; Zhan-Qun Yang (Engineering Structures, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Optimized irrigation level and deep vertical rotary tillage depth enhanced seed cotton yield, water-nitrogen productivity and economic benefit by reducing soil salinity: evidence from southern Xinjiang of China - Zhentao Bai; Ling Li; Zhijie Li; Pengfei Li; Tangang Wang; Junliang Fan; Ping Gong; Hongguang Liu (Irrigation Science, 2025)

Geographical origins of Angelica sinensis using functional compounds and multielement with machine learning-based fusion approaches - Ping Yu; Xinwei Yan; Jiashun Hong; Daocheng Li; Feng Xiong; Ruibin Bai; Jian Yang; Lanping Guo (Food Chemistry, 2025)

Advancing lactic acid Fermentation: Effects of micro aeration and herbal waste on red clover bioconversion - Chaosheng Liao; Mingjie Zhang; Pan Wang; Xiaolong Tang; Minghong You; Changbing Zhang; Guofu Jia; Wenlong Gou; Ning Mao; Yixiao Xie; Chao Chen; Shiqie Bai; et al. (Chemical Engineering Journal, 2025)

Identification of quinoa B3 gene family and its expression pattern in response to low temperature stress - Lingyuan Zhang; Yanbo Xia; Guofei Jiang; Xuqin Wang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Hydrochemical insights into spatiotemporal characteristics of groundwater salinization and health risk assessment of fluoride in the south bank of Yellow River irrigation area, Northwest China - Muhan Li; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Rina Wu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Environmental Geochemistry and Health, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Rapid and accurate identification of Panax ginseng origins based on data fusion of near-infrared and laser-induced breakdown spectroscopy - Jiacong Ping; Nan Hao; Xuting Guo; Peiqi Miao; Zhiqi Guan; Haiyang Chen; Changqing Liu; Gang Bai; Wenlong Li (Food Research International, 2025)

Combining stable isotopes and multi-elements with machine learning chemometric models to identify the geographical origins of Tetrastigma hemsleyanum Diels et Gilg - Lu Bai; Zixuan Zhang; Yalan Li; Shanshan Zhao; Xiaoting Yang; Chengqun Chen; Shilin Zhao; Ping Zhang; Xin Peng; Yan Zhao; Kehong Liang (Food Chemistry, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Multi-omics analysis of the accumulation mechanism of flavonoids in rice caryopsis under blue light - Ping Zhang; Yongsheng Tang; Juxiang Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Yutao Bai; Peng Qin (Plant Cell Reports, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Sulfadiazine degradation by Acinetobacter sp. strain H-3 and its applicability in soil at low temperatures - Shuang Zhao; Yi Zhang; Rongjiu Shi; Xiaolong Liang; Ping Li; Xue Bai; Siqin Han; Ying Zhang (International Biodeterioration & Biodegradation, 2025)

Structurally diverse ent-clerodanoids from the aerial parts of Isodon scoparius - Xue-Chun Jiang; Kun Hu; Xue Bai; Xing-Ren Li; Bing-Chao Yan; Su-Ping Chen; Xiao-Nian Li; Han-Dong Sun; Pema-Tenzin Puno (Phytochemistry, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Characterization and fine mapping of a white stripe leaf mutant in rice - Binhua Hu; Zhiyuan He; Xiaoli Xiang; Hui Li; Anping Du; Mingxia Wang; Yulu Bai; Lanying Wang; Cong Zhang; Ping Wang; Zhigang Pu (Genetic Resources and Crop Evolution, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

A combined experimental and theoretical study on the mechanism of catalytic oxidation of lignite to carboxylic acids by iron - Jiao-Xuan Bai; Cong Xu; Jie-Ping Wang; Rui Guo; Wei-Ze Wu; Ting Lu; Guang-Yue Li; Ying-Hua Liang (Fuel, 2024)

Discovery of anti-melanogenic components in persimmon (Diospyros kaki) leaf using LC-MS/MS-MN, AlphaFold2-enabled virtual screening and biological validation - Jiazheng Liu; Ting Xu; Jianjun Ding; Haoyue Wen; Jieru Meng; Qing Liu; Xiaomei Liu; Wei Zhang; Guo-Yuan Zhu; Zhi-Hong Jiang; Jin Gao; Li-Ping Bai (Food Chemistry, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

A clinical-radiomics nomogram based on spectral CT multi-parameter images for preoperative prediction of lymph node metastasis in colorectal cancer - Qian Li; Rui Hong; Ping Zhang; Liting Hou; Hailun Bao; Lin Bai; Jian Zhao (Clinical & Experimental Metastasis, 2024)

Plasma Zinc Levels in Patients with Diabetic Nephropathy: Is there a Relationship with NLRP3 Inflammasome Activation and Renal Prognosis? - Yuexin Zhu; Dedong Kang; Xiaoying Bai; Ping Luo; Bing Du; Bing Li (Biological Trace Element Research, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Sulfadiazine degradation by Bjerkandera adusta DH0817 at low temperatures and its cold-adaptation mechanisms - Shuang Zhao; Rongjiu Shi; Xiaolong Liang; Ping Li; Xue Bai; Yongfeng Wang; Ying Zhang (Bioresource Technology, 2024)

Negative rejection phenomenon in the mixed salt nanofiltration: Law and mechanism - Gao Xuerui; Li Ping; Qin Yuan; Bai Chengling; Gu Zhengyang; Yu Shuili (Desalination, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Deep vertical rotary tillage depths improved soil conditions and cotton yield for saline farmland in South Xinjiang - Zhijie Li; Hongguang Liu; Tangang Wang; Ping Gong; Pengfei Li; Ling Li; Zhentao Bai (European Journal of Agronomy, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Quercetin stimulates an accelerated burst of oviposition-based reproductive strategy in codling moth controlled by juvenile hormone signaling pathway - Bing Bai; Shi-Pan Zhang; Yu-Ting Li; Ping Gao; Xue-Qing Yang (Science of The Total Environment, 2024)

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Factors controlling the heavy metal ion activity in soil contaminated by microplastics with different mulch durations: Partial least squares path model - Huarong Sun; Yilan Shi; Chaohang Li; Siran He; Yinghao Bai; Ping Zhao; Dan Qiu; Jiamin Liu; Shuran He (Journal of Hazardous Materials, 2024)

Study on characterization and distribution of four regions of tight sandstone condensate gas reservoirs in the depletion development process - Xiliang Liu; Hao Chen; Zhihai Chen; Ran Yang; Liyang Song; Mingxing Bai; Ping Qiu; Mingsheng Zuo; Borui Li; Baoxi Yang; Xuankai Jiang; Yuting Wu; et al. (Fuel, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Erratum to: CD146 as a promising therapeutic target for retinal and choroidal neovascularization diseases - Bai Xue; Ping Wang; Wenzhen Yu; Jing Feng; Jie Li; Rulian Zhao; Zhenglin Yan; Xiyun Yan; Hongxia Duan (Science China Life Sciences, 2024)

Climate warming enhances chemical weathering in permafrost-dominated eastern Siberia - Ping Wang; Qiwei Huang; Shiqi Liu; Yu Liu; Zehong Li; Sergey P. Pozdniakov; Tianye Wang; Ekaterina S. Kazak; Natalia L. Frolova; Olga I. Gabysheva; Jialing Zhang; Bing Bai; et al. (Science of The Total Environment, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Dammarane-type saponins from Gynostemma pentaphyllum and their anti-aging activities via up-regulating mitochondria related proteins - Hai-Zhen Liang; Peng-Xin Lu; Li-Li Chu; Gang Li; Chuan-Biao Li; Xiao-Juan Chen; Jie Zhang; Juan Song; Tao Zhang; Ying Luo; Ying Hu; Bai-Ping Ma (Phytochemistry, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Eight-year comparison of agroeconomic benefits of open ditch and subsurface pipe drainage in mulched drip irrigated saline–sodic farmland - Zhentao Bai; Hongguang Liu; Jing Li; Mingsi Li; Ping Gong; Pengfei Li; Ling Li (Irrigation Science, 2023)

MLK3 localizes mainly to the cytoplasm and promotes oxidative stress injury via a positive feedback loop - Yu Jiang; Bai-Xue Wang; Yi Xie; Li Meng; Meng Li; Cai-Ping Du (Cell Biochemistry and Biophysics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Identification of new conserved linear B-cell epitopes in the 3AB and 3C protein of Senecavirus A - Jian Li; Junfang Yan; Yanni Gao; Xing Liu; Haifeng Sun; Juan Bai; Ping Jiang (Veterinary Microbiology, 2023)

Comprehensive analysis of the key amino acid substitutions in the polymerase and NP of avian influenza virus that enhance polymerase activity and affect adaptation to mammalian hosts - Yanna Guo; Tongtong Sun; Xuebing Bai; Bing Liang; Lulu Deng; Yiqing Zheng; Mengqi Yu; Yinjing Li; Jihui Ping (Veterinary Microbiology, 2023)

Effect of phosphorus on viscosity-temperature behavior of high-sodium coal ash slag - Xianxian Zhang; Haoyu Dou; Jin Bai; Lingxue Kong; Wei Feng; Huaizhu Li; Zhenxing Guo; Zongqing Bai; Ping Li; Wen Li (Fuel, 2023)

TRIM7 inhibits encephalomyocarditis virus replication by activating interferon-β signaling pathway - Minjing Li; Junfang Yan; Huixin Zhu; Chengyi Guo; Xiaolin Jiang; Yanni Gao; Xing Liu; Ping Jiang; Juan Bai (Veterinary Microbiology, 2023)

SOV sensitizes gastric cancer cells to radiation by suppressing radiation-induced autophagy in vitro and in vivo - Wen Wang; Xiao-gan Jiang; Ya-ping Bai; Heng Li; Ling-xi Gao; Teng Zhang; Fang-yi Dong; Wen-ping Ding; Yan Zhang (Tissue and Cell, 2023)

The critical condition and kinetics of interaction between residual char and slag in the coal slagging gasifier - Ji Wang; Zongshuai Yuan; Lingxue Kong; Huaizhu Li; Jin Bai; Zhiqing Wang; Zongqing Bai; Ping Li; Wen Li (Fuel, 2023)

Exogenous Ethylene Promotes the Germination of Cotton Seeds Under Salt Stress - Haipeng Li; Hongchun Sun; Wenchao Ping; Liantao Liu; Yongjiang Zhang; Ke Zhang; Zhiying Bai; Anchang Li; Jijie Zhu; Cundong Li (Journal of Plant Growth Regulation, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Molecular imprinted electrochemical sensor for ovalbumin detection based on boronate affinity and signal amplification approach - Hao Fu; Zhenyu Bai; Ping Li; Xiaoyang Feng; Xueping Hu; Xingliang Song; Lingxin Chen (Food Chemistry, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Periploca sepium leaf dry weight, area, and thickness scale differently under different light environments in Taohe riparian forests - Min Ma; Cheng-Zhang Zhao; Man-Ping Kang; Xiao-Ya Li; Zhi-Wei Zhang; Xu-Qian Bai (Flora, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Seismic behavior of concrete columns with ends transformed via perforated H-shaped steel and engineered cementitious composite - Chong Bai; Li-min Tian; Ping Yang; Tian-ji Li (Soil Dynamics and Earthquake Engineering, 2023)

Multi-objective optimization of winter irrigation for cotton fields in salinized freeze-thaw areas - Ling Li; Hongguang Liu; Ping Gong; En Lin; Zhentao Bai; Pengfei Li; Chunxia Wang; Jing Li (European Journal of Agronomy, 2023)

Late Holocene glacier variations indicated by the δ18O of ice core enclosed gaseous oxygen in the central Tibetan Plateau - Jiu-le Li; Bai-qing Xu; Ning-lian Wang; Ping Yao; Xiang-ke Xu (Journal of Mountain Science, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Photo-induced self-reduction enabling ultralow threshold voltage energy-conservation electrochromism - Zhiyuan Bai; Ran Li; Lu Ping; Qingchao Fan; Ziqiu Lu; Chengyi Hou; Qinghong Zhang; Yaogang Li; Kerui Li; Xi Ling; Hongzhi Wang (Chemical Engineering Journal, 2023)

MdbHLH51 plays a positive role in anthocyanin accumulation in ‘Red Delicious’ apples - Gai-Xing Ning; Wen-Fang Li; Ming-Yu Chu; Zong-Huan Ma; Ping Wang; Juan Mao; Bai-Hong Chen (Trees, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Evaluating the performance of hydrological models with joint multifractal spectra - Zhixu Bai; Yue-Ping Xu; Suli Pan; Li Liu; Zixia Wang (Hydrological Sciences Journal, 2022)

Administration of mesenchymal stem cells in diabetic kidney disease: mechanisms, signaling pathways, and preclinical evidence - Yuexin Zhu; Manyu Luo; Xue Bai; Yan Lou; Ping Nie; Shan Jiang; Jicui Li; Bing Li; Ping Luo (Molecular and Cellular Biochemistry, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

CD146 as a promising therapeutic target for retinal and choroidal neovascularization diseases - Bai Xue; Ping Wang; Wenzhen Yu; Jing Feng; Jie Li; Rulian Zhao; Zhenglin Yang; Xiyun Yan; Hongxia Duan (Science China Life Sciences, 2022)

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Synthesis and evaluation of ursolic acid-based 1,2,4-triazolo[1,5-a]pyrimidines derivatives as anti-inflammatory agents - Tian-Yi Zhang; Chun-Shi Li; Ping Li; Xue-Qian Bai; Shu-Ying Guo; Ying Jin; Sheng-Jun Piao (Molecular Diversity, 2022)

Influences of environmental factors on the modern 14C reservoir effects in Qinghai-Tibet Plateau lakes - Ding-ding Du; Zhi-wen Li; Hai-ping Hu; Yong-hui Bai; Wen Li; Muhammad Saleem Mughal; Hai-Yan Qian (Journal of Mountain Science, 2021)

Dynamic evolution of eukaryotic mitochondrial and nuclear genomes: a case study in the gourmet pine mushroom Tricholoma matsutake - Shu Zhang; Xue Bai; Li‐Yuan Ren; Hui‐Hui Sun; Hui‐Ping Tang; Lu‐Min Vaario; Jianping Xu; Yong‐Jie Zhang (Environmental Microbiology, 2021)
Summary Fungi, as eukaryotic organisms, contain two genomes, the mitochondrial genome and the nuclear genome, in their cells. How the two genomes evolve and correlate to each other is debated. Herein, taking the gourmet pine mushroom Tricholoma matsutake as an example, we performed comparative mitogenomic analysis using samples collected from diverse locations and compared the evolution of the two genomes. The T. matsutake mitogenome encodes 49 genes and is rich of repetitive and non‐coding DNAs. Six genes were invaded by up to 11 group I introns, with one cox1 intron cox1P372 showing presence/absence dynamics among different samples. Bioinformatic analyses suggested limited or no evidence of mitochondrial heteroplasmy. Interestingly, hundreds of mitochondrial DNA fragments were found in the nuclear genome, with several larger than 500 nt confirmed by PCR assays and read count comparisons, indicating clear evidence of transfer of mitochondrial DNA into the nuclear genome. Nuclear DNA of T. matsutake showed a higher mutation rate than mitochondrial DNA. Furthermore, we found evidence of incongruence between phylogenetic trees derived from mitogenome and nuclear DNA sequences. Together, our results reveal the dynamic genome evolution of the gourmet pine mushroom.

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Transcriptomic analysis of saffron at different flowering stages using RNA sequencing uncovers cytochrome P450 genes involved in crocin biosynthesis - Guangchun Gao; Jiming Wu; Bai Li; Qi Jiang; Ping Wang; Jun Li (Molecular Biology Reports, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

Effect of cold-anesthetization rate on blood biochemical parameters and muscle composition during live channel catfish Ictalurus punctatus waterless preservation - Chan Bai; Guangquan Xiong; Ping Xu; Ning Li; Juguang Wang; Tao Liao (Fisheries Science, 2020)

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Antioxidant coumarin and pyrone derivatives from the insect-associated fungus Aspergillus Versicolor - Tian-Xiao Li; Dan-Dan Meng; Ying Wang; Jin-Lu An; Jia-Feng Bai; Xue-Wei Jia; Chun-Ping Xu (Natural Product Research, 2020)

Deepened winter snow cover enhances net ecosystem exchange and stabilizes plant community composition and productivity in a temperate grassland - Ping Li; Emma J. Sayer; Zhou Jia; Weixing Liu; Yuntao Wu; Sen Yang; Chengzhang Wang; Lu Yang; Dima Chen; Yongfei Bai; Lingli Liu (Global Change Biology, 2020)
Global warming has greatly altered winter snowfall patterns, and there is a trend towards increasing winter snow in semi‐arid regions in China. Winter snowfall is an important source of water during early spring in these water‐limited ecosystems, and it can also affect nutrient supply. However, we know little about how changes in winter snowfall will affect ecosystem productivity and plant community structure during the growing season. Here, we conducted a 5‐year winter snow manipulation experiment in a temperate grassland in Inner Mongolia. We measured ecosystem carbon flux from 2014 to 2018 and plant biomass and species composition from 2015 to 2018. We found that soil moisture increased under deepened winter snow in early growing season, particularly in deeper soil layers. Deepened snow increased the net ecosystem exchange of CO 2 (NEE) and reduced intra‐ and inter‐annual variation in NEE. Deepened snow did not affect aboveground plant biomass (AGB) but significantly increased root biomass. This suggested that the enhanced NEE was allocated to the belowground, which improved water acquisition and thus contributed to greater stability in NEE in deep‐snow plots. Interestingly, the AGB of grasses in the control plots declined over time, resulting in a shift towards a forb‐dominated system. Similar declines in grass AGB were also observed at three other locations in the region over the same time frame and are attributed to 4 years of below‐average precipitation during the growing season. By contrast, grass AGB was stabilized under deepened winter snow and plant community composition remained unchanged. Hence, our study demonstrates that increased winter snowfall may stabilize arid grassland systems by reducing resource competition, promoting coexistence between plant functional groups, which ultimately mitigates the impacts of chronic drought during the growing season.

Predicting plant–soil N cycling and soil N2O emissions in a Chinese old-growth temperate forest under global changes: uncertainty and implications - Weiwei Dai; Edith Bai; Wei Li; Ping Jiang; Guanhua Dai; Xingbo Zheng (Soil Ecology Letters, 2020)

Macrolide sesquiterpene pyridine alkaloids from the stems of Tripterygium regelii - Dongsheng Fan; Ting Li; Zhiyuan Zheng; Guo-Yuan Zhu; Xiaojun Yao; Zhi-Hong Jiang; Li-Ping Bai (Journal of Natural Medicines, 2019)

Characterizing the Mass Elevation Effect across the Tibetan Plateau - Fang Han; Bai-ping Zhang; Fang Zhao; Li Wan; Jing Tan; Tian Liang (Journal of Mountain Science, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

QTL mapping of agronomically important traits in sorghum (Sorghum bicolor L.) - Chunming Bai; Chunyu Wang; Ping Wang; Zhenxing Zhu; Ling Cong; Dan Li; Yifei Liu; Wenjing Zheng; Xiaochun Lu (Euphytica, 2017)

Adhesion of bone marrow mesenchymal stem cells on porous titanium surfaces with strontium-doped hydroxyapatite coating - Dan-Li Fu; Qiao-hong Jiang; Fu-ming He; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Solanerioside A, an unusual 14,15-dinor-cyclophytane glucoside from the leaves of Solanum erianthum - Shi-yi Peng; Hang Li; De-po Yang; Bai Bai; Long-ping Zhu; Qin Liu; Juan Shen; Zhi-min Zhao (Natural Product Research, 2017)

Genomic and proteomic characterization of SE-I, a temperate bacteriophage infecting Erysipelothrix rhusiopathiae - Wentao Yuan; Yaning Zhang; Guangcao Wang; Juan Bai; Xianwei Wang; Yufeng Li; Ping Jiang (Archives of Virology, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Chip-based visual detection of microRNA using DNA-functionalized gold nanoparticles - Ping Wang; Jianlong Zhao; Bin Hu; Zule Cheng; Yanan Bai; Qinghui Jin; Huiying Liu; Hongju Mao; Sanqiang Li; Jianlong Zhao (Science China Life Sciences, 2016)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Functions for the cAMP/Epac/Rap1 Signaling Pathway in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Lipophilic constituents from two processed products and three different parts of Changium smyrnioides Wolff. - Gang-Gang Bai; Fei Yuan; Fu-Qiang Li; Kun-Jun Mao; Ping Zhou; Jian-Wei Chen; Xiang Li (Natural Product Research, 2015)

Role of cAMP-Dependent Protein Kinase A Activity in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu (Journal of Molecular Neuroscience, 2015)

Two new triterpenoid saponins obtained by microbial hydrolysis with Alternaria alternata AS 3.6872 - Li-Hua Mu; Yong-Jie Gu; Bai-Ping Ma; Li Lu; Ping Liu (Natural Product Research, 2015)

Asymmetric dimethylarginine triggers macrophage apoptosis via the endoplasmic reticulum stress pathway - Dan Hong; Hai-Chao Gao; Xiang Wang; Ling-Fang Li; Chuan-Chang Li; Ying Luo; Kang-Kai Wang; Yong-Ping Bai; Guo-Gang Zhang (Molecular and Cellular Biochemistry, 2015)

Proteomic alteration of PK-15 cells after infection by porcine circovirus type 2 - Jie Liu; Juan Bai; Lili Zhang; Chengcai Hou; Yufeng Li; Ping Jiang (Virus Genes, 2014)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Expression and localization of transcription factors SNAIL and SLUG in mouse ovaries and pre-implantation embryos - Cui Guo; Xiaoqian Meng; Jing Bai; Cheng Chen; Tao Liu; Shuzhen Liu; Cong Zhang; Wei-Ping Li (Cell and Tissue Research, 2014)

A new porcine reproductive and respiratory syndrome virus strain with highly conserved molecular characteristics in its parental and attenuated strains - Xing Liu; Yufeng Li; Qi Lu; Juan Bai; Xiaoye Wang; Ping Jiang (Virus Genes, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Profiles, sources, and transport of polycyclic aromatic hydrocarbons in soils affected by electronic waste recycling in Longtang, south China - De-Yin Huang; Chuan-Ping Liu; Fang-Bai Li; Tong-Xu Liu; Cheng-Shuai Liu; Liang Tao; Yan Wang (Environmental Monitoring and Assessment, 2014)

Proteomic Analysis Points to a Role for RAD23 in Apical Dominance in Pinus sylvestris var. Mongolica - De-Li Ning; Tian-Chong Lu; Gui-Feng Liu; Chuan-Ping Yang; Bai-Chen Wang (Plant Molecular Biology Reporter, 2013)

DNA binding, antitumor activities, and hydroxyl radical scavenging properties of novel oxovanadium(IV) complexes with substituted isoniazid - Xiangwen Liao; Jiazheng Lu; Peng Ying; Ping Zhao; Yinliang Bai; Wenjie Li; Mingpei Liu (JBIC Journal of Biological Inorganic Chemistry, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

New kaurene diterpenoid glycosides from fenugreek seeds - Xu Pang; Li-Ping Kang; He-Shui Yu; Yang Zhao; Cheng-Qi Xiong; Jie Zhang; Bai-Ping Ma (Natural Product Research, 2013)

Label-free quantitative proteomics analysis of dormant terminal buds of poplar - De-Li Ning; Chang-Cai Liu; Jin-Wen Liu; Zhuo Shen; Su Chen; Feng Liu; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2013)

P2X7 receptors in cerebral ischemia - Hui-Yu Bai; Ai-Ping Li (Neuroscience Bulletin, 2013)

Transforming growth factor-β1 induces matrix metalloproteinase-9 expression in rat vascular smooth muscle cells via ROS-dependent ERK–NF-κB pathways - Hao Zhang; Zhi-Wei Wang; Hong-Bing Wu; Zhi Li; Luo-Cheng Li; Xiao-Ping Hu; Zong-Li Ren; Bai-Jun Li; Zhi-Peng Hu (Molecular and Cellular Biochemistry, 2012)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

Genomic organization and sequence dynamics of the AvrPiz-t locus in Magnaporthe oryzae - Ping Li; Bin Bai; Hong-yan Zhang; Heng Zhou; Bo Zhou (Journal of Zhejiang University-SCIENCE B, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

Inhibition of encephalomyocarditis virus replication by shRNA targeting 1D and 3AB genes in vitro and in vivo - Juan Bai; Kangfu Jiang; Basit Zeshan; Xianwei Wang; Yufeng Li; Ping Jiang (Virus Genes, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Clinical characteristics of critical patients with pandemic influenza A (H1N1) virus infection in Chengdu, China - Li-hui Deng; Yi-lan Zeng; Ping Feng; Ya-ling Liu; Li-chun Wang; Yun Bai; Hong Tang (Journal of Zhejiang University-SCIENCE B, 2012)

Overexpression of the trehalose-6-phosphate synthase gene OsTPS1 enhances abiotic stress tolerance in rice - Hao-Wen Li; Bai-Sheng Zang; Xing-Wang Deng; Xi-Ping Wang (Planta, 2011)

Seismic wavefront evolution of multiply reflected, transmitted, and converted phases in 2D/3D triangular cell model - Chao-ying Bai; Xiao-ling Li; Xiao-ping Tang (Journal of Seismology, 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Increase of cytosolic calcium induced by trichosanthin suppresses cAMP/PKC levels through the inhibition of adenylyl cyclase activity in HeLa cells - Qingsong Jiang; Tumen Bai; Shunhua Shen; Lei Li; Haoliang Ding; Ping Wang (Molecular Biology Reports, 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

Early Paleogene stratigraphic sequences, mammalian evolution and its response to environmental changes in Erlian Basin, Inner Mongolia, China - YuanQing Wang; Jin Meng; Christopher K. Beard; Qian Li; XiJun Ni; Daniel L. Gebo; Bin Bai; Xun Jin; Ping Li (Science China Earth Sciences, 2010)

Remote chlorophyll- a retrieval in Case-II waters using an improved model and IRS-P6 satellite data - Jing-Ping Xu; Fang Li; Bai Zhang; Xing-Fa Gu; Tao Yu (International Journal of Remote Sensing, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Lead and Other Elemental Content of Normal and Erwinia carotovora Infected Amorphallus konjac Corms - Tao Li; Wen-Guo Wei; Wei Shao; Bai-Ling Chen; Ying-Ping Huang (Bulletin of Environmental Contamination and Toxicology, 2010)

ThPOD3, a truncated polypeptide from Tamarix hispida, conferred drought tolerance in Escherichia coli - Xiao-Hong Guo; Jing Jiang; Bai-Chen Wang; Hui-Yu Li; Yu-Cheng Wang; Chuan-Ping Yang; Gui-Feng Liu (Molecular Biology Reports, 2010)

Phosphoproteomic identification and phylogenetic analysis of ribosomal P-proteins in Populus dormant terminal buds - Chang-Cai Liu; Tian-Cong Lu; Hua-Hua Li; Hong-Xia Wang; Gui-Feng Liu; Ling Ma; Chuan-Ping Yang; Bai-Chen Wang (Planta, 2010)

A new dinorclerone diterpenoid glycoside from Tinospora sinensis - Lang-Ping Dong; Chang-Xiang Chen; Wei Ni; Bai-Bo Xie; Jun-Zhu Li; Hai-Yang Liu (Natural Product Research, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Pathogenesis of Parkinson’s disease: oxidative stress, environmental impact factors and inflammatory processes - Hong Yuan; Jing-Chen Zheng; Ping Liu; Shao-Feng Zhang; Jian-Yang Xu; Li-Min Bai (Neuroscience Bulletin, 2007)

Spatial variability of Soil Nutrients and Influencing Factors in a Vegetable Production Area of Hebei Province in China - Shao-Wen Huang; Ji-Yun Jin; Li-Ping Yang; You-Lu Bai (Nutrient Cycling in Agroecosystems, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Biodiversity and conservation in the Tibetan Plateau - Zhang Bai-ping; Chen Xiao-dong; Li Bao-lin; Yao Yong-hui (Journal of Geographical Sciences, 2002)